The Role of Financial Analysis in Improving Project Evaluation Decisions:A Case Study in the Iraqi Oil Sector - Shahad Hassoun Radi Atiyah (Academia Open, 2025)
General Background: Investment decisions in the oil sector require rigorous financial evaluation due to high capital intensity, long project life cycles, and exposure to price volatility. Specific Background: In the Iraqi oil sector, project appraisal practices often rely on limited or uneven application of modern financial analysis tools, despite their relevance for large-scale field development. Knowledge Gap: Empirical evidence remains insufficient regarding how integrated financial indicators systematically inform project evaluation and decision-making under Iraq’s specific operational and institutional conditions. Aims: This study examines the role of financial analysis in improving project evaluation decisions through an applied case study of the Majnoon Oil Field, focusing on Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. Results: The findings indicate a positive NPV exceeding USD 1.8 billion, an IRR of approximately 17% above the assumed discount rate, and an acceptable payback period, confirming the project’s economic feasibility despite cost and price uncertainties. Novelty: The study integrates theoretical financial analysis with a context-specific applied model tailored to the Iraqi oil environment, linking quantitative indicators directly to development and investment decisions. Implications: Strengthening financial analysis frameworks and integrating them with technical data can enhance evaluation accuracy, improve resource allocation efficiency, and support more reliable investment decisions within national oil companies.Highlight : Financial analysis tools support feasibility assessment in capital-intensive oil projects. The Majnoon Oil Field case shows the role of indicators under price volatility. Financial analysis strengthens investment decisions and resource allocation. Keywords : Financial Analysis, Oil Project Evaluation, Majnoon Oil Field, Investment Decision, Financial Indicators